EQUIVALENCE AND ADEQUACY ISSUES IN THE ENGLISH TRANSLATIONS OF 20TH-CENTURY UZBEK PROSE (Global Conference on Multidisciplinary Research and Innovation, 2026)
This article examines the issues of equivalence and adequacy in the English translations of twentieth-century Uzbek prose. It explores the linguistic, cultural, stylistic, and pragmatic challenges encountered in translating nationally specific elements, idiomatic expressions, historical references, and artistic imagery. Particular attention is paid to the strategies employed by translators to preserve the semantic content, aesthetic value, and cultural identity of the original texts. The study highlights the significance of achieving both semantic equivalence and communicative adequacy in literary translation while maintaining the national and cultural uniqueness of Uzbek prose. The findings contribute to a deeper understanding of translation theory and practice in the context of intercultural literary communication.
Keywords: literary translation, equivalence, adequacy, Uzbek prose, English translation, translation strategies, cultural realia, pragmatics, stylistics, intercultural communication.